Return to Palmyra (The Biblical archaeology review, 2021)
During the Hellenistic and Roman periods, Palmyra (Tadmor, in Arabic), which is in central Syria, was an important caravan city, reaching its zenith in the second and third centuries C.E. On the border between the Roman and Parthian empires, Palmyra stood at a crossroads of cultures and religions. The artifacts and surviving buildings testify […]